Clinical, Morphological Justification and First Experience in the Use of Radiofrequency as well as Microwave Ablation Treatment Methods of Liver Echinococcosis - Alexey Shabunin; Alexey Karpov; Vladimir Bedin; Mikhail Tavobilov; Grigoriy Chechenin; Sergey Lebedev; Natalia Ivanova; Anatoly Malishev; Mark Aladin; Kirill Abramov (Iranian Journal of Parasitology, 2023)
Background: The current study considers a new direction of surgical treatment of liver echinococcosis - the use of minimally invasive treatment methods of parasitic cysts.